2014
DOI: 10.3311/ppch.7123
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of aroma compounds from model solution by pervaporation membrane

Abstract: The aim of our study was to examine applicability of pervaporation in reference to the apple aroma recovery and the effects of the operating parameters on the process. Based on performed experiments the pervaporation, as membrane process, may be capable to reduce the loss of aroma compounds in the beverages production, due to its low operating temperature and high aroma recovery efficiency so organoleptic characteristics of the products would satisfy the growing consumer expectations as well. The studied main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Pervaporation is a membrane process with an important application in the recovery or concentration of flavor and aroma compounds in the food industry (Lipnizki et al, 2002). Studies on the separation of aroma compounds from juices such as orange (Aroujalian & Raisi, 2007), kiwifruit (Figoli et al, 2010), strawberry (Isci, Sahin, & Sumnu, 2006), passionfruit (Pereira et al, 2005), apple (Olsson & Trägårdh, 1999), grape (Rajagopalan & Cheryan, 1995), and pomegranate (Raisi, Aroujalian, & Kaghazchi, 2008) juice showed that pervaporation process could provide high separation factors at low temperature in binary and multicomponent solutions and real fruit juice (Hornyák, Hornyák-Holczman, Márki, & Vatai, 2014). The high efficiency of this technique in the separation of aroma compounds from low-concentration solutions has also been confirmed (Hornyák et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pervaporation is a membrane process with an important application in the recovery or concentration of flavor and aroma compounds in the food industry (Lipnizki et al, 2002). Studies on the separation of aroma compounds from juices such as orange (Aroujalian & Raisi, 2007), kiwifruit (Figoli et al, 2010), strawberry (Isci, Sahin, & Sumnu, 2006), passionfruit (Pereira et al, 2005), apple (Olsson & Trägårdh, 1999), grape (Rajagopalan & Cheryan, 1995), and pomegranate (Raisi, Aroujalian, & Kaghazchi, 2008) juice showed that pervaporation process could provide high separation factors at low temperature in binary and multicomponent solutions and real fruit juice (Hornyák, Hornyák-Holczman, Márki, & Vatai, 2014). The high efficiency of this technique in the separation of aroma compounds from low-concentration solutions has also been confirmed (Hornyák et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When the traditional separation method, such as multiple effect evaporation, was used, the quality of the end product is deteriorated. Also, conventional processes consume high energy . In conventional processes, it is not possible to avoid the effect of the temperature on the aroma, and additives should be used.…”
Section: Introductionmentioning
confidence: 99%
“…Still, academic studies centre upon the pervaporative desulfurization, aroma recovery, chemical synthesis, waste treatment, and desalination processes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%